Urban water demand detection device based on SPSS - YAO WANSEN; AN GUORUI; LIU YATAO; YU JIANZHOU (2021)
The utility model discloses an SPSS-based urban water demand detection device, which comprises a body, a wall body is arranged on the rear side of the body, a supporting plate is fixedly connected to the front side of the wall body, shells are fixedly connected to the two sides of the body, limiting grooves are formed in the rear sides of the shells, limiting rods are fixedly connected to the two sides of the front side of the wall body, and the limiting rods are fixedly connected to the front side of the body. The front side of the limiting rod extends to an inner cavity of the limiting groove, and a fixing mechanism used in cooperation with the limiting rod is arranged in the inner cavity of the shell. By arranging the body, the wall body, the supporting plate, the shell, the limiting groove, the limiting rod, a fixing mechanism, a fixing rod, a supporting rod, a spring, a positioning block, a movable mechanism, a pull rod, a movable plate, a movable block, a fixing hole, a movable hole and a fixing groove